Chest computed tomography scan as an initial diagnostic method for tuberculosis infection detected by mass screening - Dong-Hyun Joo (The Korean Association of Internal Medicine, 2021)
Background/Aims We assessed the diagnostic yield of chest computed tomography (CT) as an initial diagnostic method for patients with a tuberculosis (TB) infection detected by mass screening in a country with an intermediate TB burden. Methods A retrospective study was conducted on patients with TB infection detected by mass screening performed between January 2015 and March 2018. The patients were classified according to whether they had a chest X-ray (CXR) or CT scan as an initial diagnostic test to exclude active TB. Results Of 542 patients with TB infection detected by mass screening, 222 and 320 were initially examined by CXR and CT, respectively; the two modalities showed no significant difference in rate of detection of patients with active TB (0.9% and 2.5%, respectively; p = 0.110). However, chest CT was associated with further invasive tests using bronchoscopy and respiratory specimens, and significantly increased the frequency of hospital visits. Conclusions Chest CT was not supported as an initial diagnostic method to rule out active TB in patients with a TB infection detected by mass screening in a country with an intermediate TB burden.